Current trends in gynecology research in Colombia: A brief bibliometric analysis - Santiago Serna, Juan (2024)
Gynecology, as a specialized field in female reproductive health, operates in a dynamic environment shaped by demographic changes, technological advancements, and evolving pathophysiological understandings. Researching trends in this discipline is not only essential for maintaining the quality of care but also serves as a fundamental pillar for advancing medical knowledge. Identifying these trends provides an invaluable opportunity to recognize knowledge gaps, highlighting research areas that require prioritized attention. Through a rigorous approach to identifying and addressing these gaps, the generation of new knowledge and therapeutic innovation is promoted. This approach, supported by a thorough analysis of emerging trends, can catalyze the formulation of clinical hypotheses, the execution of prospective studies, and the development of more effective therapeutic interventions. Ultimately, this continuous pursuit of scientific evidence contributes to optimizing both clinical and non-clinical outcomes in gynecological care, thereby driving excellence in medical practice and improving patients' quality of life.